Yaws active case detection surveys in 15 districts of Cote d’Ivoire - Aboa Paul Koffi; Didier Yao Koffi; Elysée Gobe Agodio; Théodore Yao; N’cho Mouroh Chantal N’guessan; Amari Jules Cesar Akpa; Eguzkiñe Muñoz Trevilla; Notie Berté; N’zebo N’goran; Nzrasse Florent Niamke; Agui Sylvetre Dizoe; N’goran Raphael N’dri; et al. (PLoS ONE, 2026)
Background Yaws is one of the skin-related neglected tropical disease (skin NTD). It is closely linked to poverty and occurs mainly in poor communities in hot, humid, tropical regions. Children in disadvantaged communities in the tropics are most affected. Following the recommendations of the WHO NTD Road map 2021–2030, Côte d’Ivoire planned an evaluation (clinical and serological investigation) to assess the true extent of yaws in the country. Côte d’Ivoire is one of the nine countries currently endemic for yaws in the WHO African Region. The aim of this investigation was to establish the endemicity of yaws and to gather information that will inform planning for yaws eradication in Côte d’Ivoire. Method A public health intervention involving active case-finding was conducted in 345 health areas of 15 targeted health districts. All children aged 2–15 years in village primary schools and in households were systematically recruited and examined. All enrolled children with suspicious lesions were initially tested with Standard Diagnostic (SD) serological treponemal test. Cases positive for treponemal SD test were subsequently tested using the dual treponemal and non-treponemal point-of-care test (DPP), a rapid serological test that is used to confirm yaws. All confirmed cases were treated with a single dose of azithromycin according to age. Additionally, other skin NTD and skin conditions were detected. Results A total of 3870 villages and hamlets were investigated in which 486 975 children were targeted. Overall, 65 918 (14.66%) children with various skin lesions were identified. Two hundred and ninety-one (291) RDT (Rapid Diagnostic Test) positive cases of yaws were documented. Half of the RDT positive cases (146/291) were confirmed as DPP positive. Children aged 5–14 years ( n = 129) represented 88% of DPP positive cases. The four most common skin conditions identified were traumatic wounds (13 855; 21.07%), dermatophytosis (15 640; 23.8%), pityriasis versicolor (6998; 10.64%) and scabies (5955; 9.05%). Conclusion This rapid investigation confirmed the endemicity of yaws in Côte d’Ivoire at low and variable prevalence. Treatment interventions will be adapted to the level of endemicity that we have found. Analysis of the results opens avenues of research to better understand the endemicity of yaws in Côte d’Ivoire.